Blue and white solution-processed TADF-OLEDs with over 20% EQE, low driving voltages and moderate efficiency decrease based on interfacial exciplex hosts. Issue 38 (11th September 2019) - He, Zeyu; Wang, Chenyu; Zhao, Juewen; Du, Xiaoyang; Yang, Haoyu; Zhong, Pingli; Zheng, Caijun; Lin, Hui; Tao, Silu; Zhang, Xiaohong
Abstract : Blue and white solution-processed OLEDs with low driving voltages, over 20% maximum external quantum efficiency and moderate efficiency decrease were realized by using interfacial exciplex hosts. Abstract : Solution-processed organic light-emitting diodes (OLEDs) based on thermally activated delayed fluorescence (TADF) emitters have great prospects for large area solid-state lighting and flexible displays due to low-cost fabrication and a simple production technique. However, blue solution-processed TADF-OLEDs encounter challenges of low efficiency, high driving voltage and severe efficiency decrease. In this work, three interfacial exciplexes were used as hosts to develop efficient blue solution processed TADF-OLEDs. Among them, the optimized blue OLED based on a CDBP/PO-T2T host realized a maximum external quantum efficiency (EQE) of 21.0%, a low turn-on voltage of 3.6 V and driving voltages of 4.4 V at 100 cd m −2 and 5.8 V at 1000 cd m −2 . It is important to note that the EQE of the device remains at 20.2% and 13.6% at 100 cd m −2 and 1000 cd m −2, respectively. Moreover, a color-stable hybrid white OLED was developed based on this blue system. The optimized white device exhibited a high maximum EQE of 20.8% and EQEs of 20.2% and 11.8% at 100 cd m −2 and 1000 cd m −2, and is among the best reported white solution-processed OLEDs based on blue TADF emitters. These results demonstrate that the interfacial exciplex would be a suitable host for future solution-processed TADF-OLEDs.